2011
DOI: 10.1007/s00436-011-2425-1
|View full text |Cite
|
Sign up to set email alerts
|

Contact and fumigant toxicity of hexane flower bud extract of Syzygium aromaticum and its compounds against Pediculus humanus capitis (Phthiraptera: Pediculidae)

Abstract: The head lice, Pediculus humanus capitis De Geer is an obligate ectoparasite of humans that causes pediculosis capitis, a nuisance for millions of people worldwide, with high prevalence in children. P. humanus capitis has been treated by methods that include the physical remotion of lice, various domestic treatments, and conventional insecticides. None of these methods render complete protection, and there is clear evidence for the evolution of resistance and cross-resistance to conventional insecticides. Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 69 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…The 2 compounds were identified to be moupinamide and physalin I, and a third unknown compound with a m/z of 230.2471. The structural aspect of these compound may contribute to the pediculicidal efficacy [ 41 43 ]. Moupinamide belongs to the class benzenoids, and its direct parent methoxyphenol [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2 compounds were identified to be moupinamide and physalin I, and a third unknown compound with a m/z of 230.2471. The structural aspect of these compound may contribute to the pediculicidal efficacy [ 41 43 ]. Moupinamide belongs to the class benzenoids, and its direct parent methoxyphenol [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Bagavan et al 2011; Mehlhorn et al 2011; Abdel-Ghaffar et al 2012) analyzed the effect of natural products against both motile lice and eggs. In particular, Abdel-Ghaffar et al (2012) propose an antilice shampoo based on a new seed extract able to be efficacious after one treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Abdel-Ghaffar et al (2012) propose an antilice shampoo based on a new seed extract able to be efficacious after one treatment. The hexane flower bud extract of S. aromaticum ( Myrtaceae ) was evaluated by Bagavan et al (2011), who found a major effect in vapor phase. These studies underline that natural products may provide good antilice activity and can offer a valid alternative to conventional insecticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasingly poor performance of neurotoxic head lice treatments and the growing public concern over their use has led to an increase in the commercialisation of alternative treatments . Plant essential oils and their constituents provide a rich source of bioactive chemicals that are easily extractable and biodegradable and generally have low mammalian toxicity . However, very few in vitro and clinical studies have evaluated the effectiveness of these alternative compounds, and the bulk remain to be scientifically tested…”
Section: Introductionmentioning
confidence: 99%